Towards Sustainable Living: Improving Living Conditions of Low-Income Workers in Bahrain’s Labour Camps - Avni Durga Hemanth; Fay Abdulla Al Khalifa (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The reliance on migrant workers in the GCC countries has led to various challenges, particularly regarding the living conditions of these workers in labour camps. These accommodations are often, overcrowded and lack essential amenities contributing to health and social issues among the occupants. This paper aims to explore the living conditions of low-income workers in Bahrain’s labour camps identifying challenges regarding their housing quality, access to services and social intergration. Applying a mixed methods approach in the form of surveys, interviews and case studies the paper explores ways to improve their livelihoods while promoting sustainable living. The study findings highlight issues such as inadequate ventilation, poor sanitation, and social isolation. The study proposes design interventions, including improved ventilation, better communal spaces, and sustainable housing solutions. The findings of the study contribute to the discourse on labour housing and offers insights to promote more inclusive, healthy, and sustainable living environments among low-income workers.